Bitcoin аnd the “Fourth Wave” of Globalization - Radulović, Srđan M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The tendency to transform individual social communities into a universal, unified society which knows no boundaries (or at least does not insist on them), with the necessary dose of simplification, is the conceptual definition of globalization. Since it is a tendency, globalization naturally has its own temporal dimension. The process of determining the time coordinates of this phenomenon is extremely complex and the results may vary depending on the scientific approach and point of view. However, we believe that it is possible to reach a consensus that the process of globalization is not continuous, but has several phases. We tend to think that there are three main phases of globalization. Of course, we fully respect other competing systems of periodization and argumentation on which they are based. Nevertheless, we do not doubt that proponents of different periodization would agree that a new phase of globalization began recently, although it is difficult to determine the exact moment when it was initiated. Namely, on October 31, 2009, a mysterious developer, or more likely group of developers, behind the fictious name of Satoshi Nakamoto, published the so-called White Paper titled Bitcoin: A Peer-to-Peer Electronic Cash System. More than ten years later, on March 11, 2020, the World Health Organization declared the outbreak of SARS-CoV-2 pandemic. These two, at first glance unrelated events cumulatively initiated chain of new transformations, all leading toward a more unified society. Probably the most important change, one that is the focus of this paper, is the transformation of centralized localized monetary systems into completely decentralized, digitalized, totally independent, almost entirely self-sustaining, and self-regulating global financial structure. This paper presents a part of the results collected through the theoretical-empirical research conducted previously on both legal and socio-economic moments that initiated a new phase of globalization. These results refer mostly to events that initiated a new phase of globalization, their connections, and problems of periodization. The remaining results, results on the scope and expected overall effects of this phase, will be presented in the next article in this series. All the results of the research and conclusions were collected based on different analytical-synthetical methods, mostly abstraction and generalization. In this paper specifically, different techniques of the normative method were used. Also, special techniques of legal norm interpretation were used in the process.